2010
DOI: 10.1016/j.antiviral.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antiviral effect of Galanthus nivalis agglutinin and nelfinavir against feline coronavirus

Abstract: Feline infectious peritonitis (FIP) is a fatal disease in domestic and nondomestic felids caused by feline coronavirus (FCoV). Currently, no effective vaccine is available for the prevention of this disease. In searching for agents that may prove clinically effective against FCoV infection, 16 compounds were screened for their antiviral activity against a local FCoV strain in Felis catus whole fetus-4 cells. The results showed that Galanthus nivalis agglutinin (GNA) and nelfinavir effectively inhibited FCoV re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 30 publications
0
53
0
Order By: Relevance
“…Ribavirin was reported to reduce the replication of FIPV with IC 50 of 10 μM and TC 50 of 69 μM, and a later study using specific pathogen free cats infected with FIPV showed that ribavirin treatment at 16.5 mg/kg was not effective at reducing fatality or severity of symptoms (Weiss et al, 1993). In addition, studies on the antiviral agents that directly or indirectly target virus components and/or replication steps are very limited (Barlough and Shacklett, 1994; Hsieh et al, 2010; Regan et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Ribavirin was reported to reduce the replication of FIPV with IC 50 of 10 μM and TC 50 of 69 μM, and a later study using specific pathogen free cats infected with FIPV showed that ribavirin treatment at 16.5 mg/kg was not effective at reducing fatality or severity of symptoms (Weiss et al, 1993). In addition, studies on the antiviral agents that directly or indirectly target virus components and/or replication steps are very limited (Barlough and Shacklett, 1994; Hsieh et al, 2010; Regan et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…A number of compounds have demonstrated an inhibitory effect on the virus in vitro (Barlough and Shacklett, 1994;Hsieh et al, 2010;Keyaerts et al, 2007), but there is little or no published data regarding their use in treating FIP. The broad spectrum antiviral ribavirin demonstrated in vitro efficacy but provided limited clinical benefit and produced toxicity in cats (Weiss et al, 1993).…”
mentioning
confidence: 99%
“…Combining chloroquine with other ''anti-FIPV agents'' overcomes this problem. Hsieh et al (2010) succeeded in inhibiting FIPV replication in fcwf-4 cells using the low-cytotoxic antiviral agents. It will be necessary to further investigate the possibility of FIP treatment with a combination of chloroquine and other agents.…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral, immunostimulating, and immunosuppressive drugs have been experimentally used for the treatment of FIP, but none of these have exhibited a sufficient therapeutic effect. Several agents that significantly inhibit FCoV replication in vitro have been identified (Balzarini et al, 2006;Barlough and Shacklett, 1994;Hsieh et al, 2010;Kim et al, 2012;Takano et al, 2008); however, whether or not these agents exhibit a therapeutic effect in cats with FIP has not been investigated.…”
Section: Introductionmentioning
confidence: 99%